Confinement of Candida Antarctica Lipase B in a Multifunctional Cyclodextrin-Derived Silicified Hydrogel and Its Application as Enzymatic Nanoreactor - Decarpigny, Cédric; Bleta, Rudina; Ponchel, Anne; Monflier, Eric (ACS Publications, 2019)
2;12